Prostate specific antigen based biennial screening is sufficient to detect almost all prostate cancers while still curable. - Hugosson, J; Aus, G; Lilja, H; Lodding, P; Pihl, C; Pileblad, E (2003)
PURPOSE: We evaluated whether biennial screening with prostate specific antigen (PSA) only is sufficient to detect prostate cancer while still curable. MATERIALS AND METHODS: In Göteborg, Sweden 9,972 men 50 to 65 years old were randomized to PSA screening. During 1995 and 1996 these men were invited for a first PSA screening and invited during 1997 and 1998 for a second screening. The screening procedure included PSA measurement in all men and in those with a PSA of 3 ng./ml. or greater also it included digital rectal examination, transrectal ultrasound and sextant biopsies. RESULTS: In the first screening 5,854 men participated and 145 cancers were detected. In the second screening 5,267 men participated and 111 cancers were detected. Only 9 interval cancers were diagnosed. In the second screening 102 cancers (92%) were associated with PSA less than 10 ng./ml. Of 465 men with increased PSA and who underwent biopsy with a benign outcome in the first screening 50 had cancer at the second screening. Of 241 men in whom PSA increased between screenings 1 and 2 cancer was detected in 46. None of the 2,950 men with an initial PSA of less than 1 ng./ml. had a PSA of greater than 3 ng./ml. or interval cancer. CONCLUSIONS: In men with a PSA of less than 2 ng./ml. it seems safe to offer repeat screening after 2 years with PSA only. Men with a PSA of 2 to 3 ng./ml. or a value of greater than 3 ng./ml. with negative biopsy may be better served by a shorter screening interval. Thus, different screening intervals are implied depending on baseline PSA.